(untitled) (Jurnal Kesehatan Komunitas, 2020)
The monthly reporting of Dengue Hemorrhagic Fever (DHF) at the Puskesmas must be sent to the Indragiri Hulu District Health Office so that it can be evaluated to reduce the number of cases of Dengue Hemorrhagic Fever (DHF). The purpose of this study was to find out whether the evaluation of monthly reporting of Dengue Hemorrhagic Fever (DHF) was carried out at the Indragiri Hulu District Health Office. This type of research is descriptive with a qualitative approach, namely by describing and explaining the implementation of the Puskesmas Dengue Hemorrhagic Fever P2 (DBD) Evaluation Program at the Indragiri Hulu District Health Office in 2019.The results of the study on the implementation of the P2 DBD Evaluation report, namely, there are still a number of Puskesmas whose content of P2 DBD reports is still incomplete, there are still a number of Puskesmas that deliver reports past the specified period, evaluation of DHF P2 reporting programs in Puskesmas conducted by the District Health Office Indragiri Hulu in the form of meetings in the quarterly period at the Health Office discusses all programs, but special evaluations on the P2 DBD program have not run efficiently, and written policies have not been available for the Indragiri Hulu District Health Office or the Puskesmas. The policy is still under construction.The conclusion is the evaluation of the P2 DBD program reporting at the Indragiri Hulu District Health Office has been carried out, but it has not been maximized. Evaluation carried out by the Health Office is an evaluation of all programs in the Puskesmas, for special evaluation on the P2 DBD reporting not yet available. It is said to be not maximal because the evaluations carried out have not been consistent, because sometimes evaluations are carried out within three months, or within four months, and there is no policy to carry out the evaluation activities. So it is advisable to make a policy and carry out a socialization about evaluating the Puskesmas DHF monthly report.